2019
DOI: 10.1177/0003489419826138
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fatigue in Head and Neck Cancer Survivors

Abstract: Introduction: In head and neck cancer (HNC) patients, fatigue is present throughout the course of treatment and during follow-up. There are limited data about the prevalence and factors associated with fatigue in HNC survivors. The objectives of this study were to assess the prevalence of fatigue and its interference with daily life activities and examine the association between fatigue and gender, age, primary tumour site, Human Papillomavirus (HPV) status, previous oncologic therapy, and time since end of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…Patients treated for head and neck cancer (HNC) have a high risk for loss of function such as swallowing, eating, and speaking, and therapy-associated side effects. Anxiety, depression, and fatigue are frequent psychological symptoms and syndromes particularly among HNC patients [1][2][3][4]. The American Head and Neck Survivorship Care Guideline defined the detection of negative psychological side effects as one major target of the tumor aftercare in addition to functional assessments and physical examinations for early detection of recurrence or secondary primary tumor [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated for head and neck cancer (HNC) have a high risk for loss of function such as swallowing, eating, and speaking, and therapy-associated side effects. Anxiety, depression, and fatigue are frequent psychological symptoms and syndromes particularly among HNC patients [1][2][3][4]. The American Head and Neck Survivorship Care Guideline defined the detection of negative psychological side effects as one major target of the tumor aftercare in addition to functional assessments and physical examinations for early detection of recurrence or secondary primary tumor [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is also a common symptom of cancer patients. Bossi et al reported an incidence of moderate to severe fatigue in 18% of their HNC patients [2]. Fatigue impairs all aspects of life, but it is also hardly comprehensible and is not easy to treat.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue affects most HANC survivors to varying levels 54 and was ranked sixth of 56 concerns that HANC survivors wished to discuss during their review consultation. 55 A recent review of the literature found strong evidence for the efficacy of exercise interventions for decreasing cancer-related fatigue, with a dose-response relationship up to 150 min•wk -1 of aerobic exercise.…”
Section: Psychological and Emotional Issuesmentioning
confidence: 99%
“…For instance, the Australian Medical Association found that out of 716 doctors, 53% were at higher risk of fatigue whilst on duty ( Australian Medical Association, 2017 ). In another study, around 85% of patients with head and neck cancer experienced fatigue ( Bossi et al, 2019 ). In addition, college students, particularly those enrolled in health-related subjects, often suffered from fatigue ( Dol, 2016 ; Pallant, Sullivan & Kaluzny, 2020 ; Shim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%